Młode kobiety w gangach: między wiktymizacją a maskulinizacją - Andraszczyk , Wojciech (Studia Edukacyjne, 2020)
In this paper I will try to present a selection of contexts of young women’s functioning in the gangs. Gangs are traditionally associated with a male identity and a masculine type of criminality, therefore a female participation in the gangs breaks up completely with the essentialist image of femininity and denies the dichotomous division of sexes. A woman as a member of a gang, with her violence oriented attitude and masculinised identity put all the former ideals into question. In this article I will also make reference to the myths concerning female gangs, which among others refer to the conviction that their female members play a secondary part, being a sort of “sattelites” to the male gangsters. Moreover, I will reconstruct the role of the female members of a gang in its structure, as well as the process of women dropping out of a gang.